Highly interconnected porous monolithic and beaded polymers using high internal phase emulsion polymerization: tuning porous architecture through synthesis variables - Ponrathnam, Timothy; Behere, Isha; Ponrathnam, Surendra; Ingavle, Ganesh (Polymer International, 2023)
Open porous polymeric materials have gained popularity due to their exceptional properties and applications in tissue engineering scaffolds, drug delivery, enzyme immobilization and catalysis support. This study developed a novel two-stage approach to create networked, crosslinked poly(2-hydroxyethyl methacrylate-co-N,N'-methylenebisacrylamide) HEMA-MBA beads. The first part involves producing an oil-in-water-in-oil high internal phase emulsion (HIPE). This is followed by suspension polymerization using a redox initiator pair. In this study, a mixed surfactant combination with low and high hydrophilicity-lipophilicity balance surfactants was identified and successfully utilized to prepare a stable oil-in-water-in-oil HIPE. The effect of crosslinker concentration (i.e. crosslink density), surfactant concentration and monomer-to-porogen ratio on pore architecture and surface area were successfully evaluated. In addition, a new protocol was developed to synthesize HEMA-MBA monoliths using an oil-in-water HIPE method at ambient temperature using a redox initiator pair. The effect of crosslink density and oil phase on pore architecture and surface area was evaluated. Key variables affecting the morphology of porous HEMA-MBA beads and monoliths were identified and quantified, allowing future development of porous HEMA-based polymer beads and monoliths with tunable morphologies which are suitable for numerous applications, especially in the biomedical field. (c) 2022 Society of Industrial Chemistry.
Keywords: HIPE polymerization; porosity; porous polymers; redox polymerization; Suspension polymerization